Kepuasan Pengguna E-Wallet: Studi pada Generasi Z di Era Digital - Novemy Triyandari Nugroho; Sundari Sundari (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of perceived usefulness, ease of use, and security on e-wallet user satisfaction among Generation Z in the digital era. A quantitative approach was employed using multiple linear regression analysis. The sample consisted of 104 respondents who are active e-wallet users and belong to Generation Z in Surakarta, Indonesia. The results indicate that perceived usefulness, ease of use, and security have a positive and significant effect on user satisfaction. Among these variables, ease of use had the most dominant influence. The coefficient of determination value of 98.4% indicates that the independent variables simultaneously explain most of the variation in user satisfaction. These findings highlight the importance of user-friendly, functional, and secure features in enhancing e-wallet satisfaction among the younger generation.